Orthognathic Surgery in Craniosynostosis. Issue 1 (January 2021) - Ferri, Joël; Schlund, Matthias; Touzet-Roumazeille, Sandrine
Abstract : Introduction: Craniosynostosis is characterized by the fusion of 1 or more sutures of the skull leading to craniofacial deformations. Our aim is to describe the dental malocclusion associated with craniosynostosis, syndromic, or nonsyndromic, and also the treatment used and its stability. Material and Methods: This retrospective study included all patients who presented at our Department for facial growth monitoring and occlusal management following syndromic and nonsyndromic craniosynostosis. Inclusion began in January 1996 and ended in December 2015 to ensure sufficient follow-up. Orthognathic surgery was performed after the end of growth. Dental occlusion was evaluated clinically and radiographically. Results: Fifty-five patients were included with 18 syndromic cases. The majority of patients presented with class III malocclusion (69.1%), especially syndromic cases (94.7%) and brachycephalies (96.3%). Conversely, scaphocephalies are associated with class II malocclusions. Thirty-nine patients underwent orthodontic treatment associated with orthognathic surgery to correct their malocclusion. In 4 cases, optimal dental occlusion was achieved with orthodontic treatment alone. Forty patients achieved stable optimal final dental occlusion. Optimal dental occlusion was achieved in 76.9% of the nonsurgically treated craniosynostosis patients and 68.9% of the surgically treated craniosynostosis patients. Discussion: Sutural fusion induces a facial growth restrictions and dental malocclusions. Several mechanisms may be responsible for these malocclusions: positional anomaly of the jaws due to the cranial deformity, associated anomaly of the facial sutures, or osteocartilagenous system diseases. Early craniosynostosis management does not avoid the occurrence of malocclusion, which will require orthodontic treatment and orthognathic surgery for their management. Abstract : Supplemental Digital Content is available in the text